Opportunity amid crisis: how climate risks drive digital governance — a dual perspective from public safety and low-carbon development - Zhang, Jing; He, Zijian (Frontiers in Environmental Science, 2026)
As global climate risks intensify, government governance systems are confronted with unprecedented pressures for transformation and new strategic opportunities. Through the dual perspectives of public safety and low-carbon development, this study systematically explores how climate risks can enhance national digital governance capacity. By constructing a panel dataset encompassing 191 countries from 2003 to 2024, it is confirmed that physical climate risks and transition risks significantly contribute to the optimization of digital governance. Moreover, efficient government services and political stability strengthen the positive impact of physical risks on digital governance, while high-carbon economic systems and fiscal debt pressures mitigate the positive impact of transition risks. The findings indicate that climate risk is not merely a threatening external factor; in countries with institutional resilience and fiscal and budgetary capabilities, it can be leveraged as a strategic opportunity to promote digital governance. This paper not only offers an integrated analytical framework for examining the interactive relationship between climate risk and digital governance but also provides theoretical and policy-relevant insights for countries formulating differentiated digital economy strategies in the context of enhancing the resilience of global climate governance.